(3eYLe GdcfGjGJ hGdJQGcjH hGdJYGHjQ GdTYHjI GdEUWdGMjI aj eOf GdMLGR, hGdeYfhf H`, eYLe GdcfGjGJ GdMLGRjI (B: s (3Chd eYLe JhKjbj ddcfGjGJ GdMLGRjI (B/s - (3SdGeI, aQjO YHO GdMejOs ((3ecI GdecQeI (B:s (3OGQ GdedJRe ddWHGYI hGdfTQ hGdJhRjY,s, 2020)
(3aj gPG GdcJGH JhKjb hJSLjd deYXe eG jNU GdMLGR hScGf eOfg, hgh hUa TGed dcd eG gh MLGRj, hgPG GdeYLe jYJHQ OQGSI ejOGfjI JJfGhd YhGde GdMLGR GddZhjI hGdPj cGf ef CSHGH LeYg hJCdjag fTCJj aj GdHjFI GdTYHjI aj Mj bHGA HGdeOjfI GdefhQI HMGQI GdRGgOjI GdQGFYI hef Ke GfJbGdj Edi eOjfI LOI dMGQI GdTGe hbQHj ef Shb GdfOi hMGQGJ GdeXdhe hGdjef hGdHMQ ahbaJ HPdc Ydi cKjQ ef gPg GdcfGjGJ GdJj SQJ Ydi dSGf GdfGS eSQi GdCeKGd hLYdhG efgG eMW GdTGgO aj CMGOjKge Ydi SHjd GdGSJYGQI hGdcfGjI hGdehGRfI hGdJTHjg(B. (3hbO Ve GdeYLe MhGdj NeSI BdGa cfGjI hJYHjQ TYHj heFGJ GdBjGJ GdbQBfjI hGdCMGOjK hGdcKjQ ef GdCHjGJ GdTYQjI hGdCgGRjL hGdCeKGd GdSGFQI hGdeCKhQI hGdMceI LeYJgG ef CahGg GdfGS ef cdGefG hMGhdJ LGOG GdHMK Yf CUhd eYXegG hcja LGAJ EdjfG(B.s
(3cTGa (B: (3UaMI (B519-570.s
Keywords: (3GddZI GdYQHjIs -- (3eYGLes -- (3dgLGJs -- (3GdSYhOjIs -- (3GdMLGRs; (3GdCeKGd GdYGejI GdYQHjIs -- (3CbhGd eCKhQIs -- (3Mces